The c-MYC-AP4-p21 cascade - Jung, Peter; Hermeking, Heiko (Cell cycle (Georgetown, Tex.), 2009)
The p21 gene encodes a CDK-inhibitor, which is induced by p53 and many other anti-proliferative factors. The mechanism of transcriptional repression of p21 by c-MYC has been a subject of intensive study for several years, as it may explain how c-MYC promotes cell cycle progression. Recently, we reported a novel mechanism which allows c-MYC to repress p21: c-MYC triggers a transcriptional cascade by directly inducing the gene encoding the bHLH-LZ transcription factor AP4 (TFAP4), which binds to recognition motifs located in the vicinity of the p21 promoter and mediates transcriptional repression of p21. Thereby, AP4 interferes with induction of p21 via the DNA damage response/p53 or TGF-β/Smad pathways and during differentiation. Intriguingly, the expression patterns of c-MYC and AP4 strictly overlap in colonic epithelium and colorectal cancer. Here we survey the recent findings and discuss the role of AP4 for c-MYC function and its potential application for cancer diagnosis and therapy.